IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN DI SD NEGERI 7 TANJUNG RAJA - Hartati, Welly (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This study aimed at describing the Implementation of discipline character in SD Negeri 7 Tanjung Raja. It is a descriptive study using qualitative approach. This research was conducted at SD Negeri 7 Tanjung Raja. Data were collected through observation, interview and documentation. The validity of the data used triagulation technique which checked or compared some data, including the components of knowledge, awareness or willingness, and actions taken in implementing discipline character. This character could not succeed as long as there were no sustainability and harmony between education environments likes household and family as the first and main character formation and education environment. To improve the quality of discipline character in education, the implementation and evaluation were needed in all level of education. The results of this study showed that the discipline character in education could change the attitudes and behavior of teachers and students of SD Negeri 7 Tanjung Raja be better, for example teachers and students would shake hands when they came or left the school, finish the ceremony in turn, and dressed neatly in accordance with the appointed day, no more students who came late or skipped school. The development and implementation of discipline character was a must do action to create the students who were accustomed to behave more disciplined.